2018
DOI: 10.1038/sj.bdj.2018.123
|View full text |Cite
|
Sign up to set email alerts
|

Are there good reasons for fluoride labelling of food and drink?

Abstract: This opinion piece highlights the importance of controlling systemic fluoride intake from food and drink in early childhood to minimise risk of dental fluorosis whilst maximising caries prevention; the wide range of fluoride contents found in a study of commercially-available food and drinks; and the need for comprehensive fluoride labelling on food and drink products in the UK, particularly those used by infants and young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…Caries preventive agents should preferably be used on a daily basis to maintain a preventive concentration of the agent in oral cavity at all times. 47 Furthermore, on a risk/benefit ratio, while high fluoride concentration dentifrices can only be used by adults due to the risk of fluorosis in children, 20,50 HAP-based dentifrices and gels at any concentration can be used by all ages since no adverse effect has been reported in previous clinical studies. 4,12,35 This would go further to eliminate having different dosages for infants, children and adults, as it is the case with fluoride at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Caries preventive agents should preferably be used on a daily basis to maintain a preventive concentration of the agent in oral cavity at all times. 47 Furthermore, on a risk/benefit ratio, while high fluoride concentration dentifrices can only be used by adults due to the risk of fluorosis in children, 20,50 HAP-based dentifrices and gels at any concentration can be used by all ages since no adverse effect has been reported in previous clinical studies. 4,12,35 This would go further to eliminate having different dosages for infants, children and adults, as it is the case with fluoride at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent classification of fluoride as a chemical neurotoxicant could raise safety concerns among the general public regarding the use of high concentration fluoride products [Grandjean and Landrigan, 2014]. More pertinent are the growing concerns that children today are exposed to fluoride from multiple sources, potentially increasing their risk of developing dental fluorosis [Zohoori and Maguire, 2018]. This "halo" effect of fluoride probably accounts for the increased prevalence of permanent tooth mottling being seen in western countries [McGrady et al, 2012;Pendrys, 2000].…”
Section: Fluoride -Improving Its Efficacy and Safetymentioning
confidence: 99%
“…The association between fluoride concentration of water and fluoride excretion was reported in 28 studies, whereas only 18 studies (9%) reported the association between fluoride intake and fluoride excretion (Table 4). Considering the multiple and increasing sources of fluoride exposure, and the rise in the “halo effect” of fluoride through globalisation of the food and drink industry [105], the relevance of studies in which fluoride concentration of water is used as a proxy for fluoride intake could be questionable. In addition, due to the diversity of the methods of data collection and analysis, geographical locations and age groups, as well as the small number of studies (n = 18) in which the relationship between fluoride intake and fluoride excretion was investigated, no firm conclusion on the appropriateness of urine as a biomarker for fluoride exposure for all age groups and all dietary/oral hygiene habits can be drawn.…”
Section: Discussionmentioning
confidence: 99%